A multi-institutional study of hemostatic gauze and tourniquets in rural civilian trauma. Issue 3 (September 2016) - Leonard, Jennifer; Zietlow, John; Morris, David; Berns, Kathleen; Eyer, Steven; Martinson, Kurt; Jenkins, Donald; Zietlow, Scott
Abstract : BACKGROUND: Life-threatening hemorrhage is a leading cause of preventable mortality in trauma patients. Since publication of the Hartford Consensus statement, there has been intense interest in civilian use of commercial hemostatic gauze and tourniquets. Although the military has studied their use on soldiers with wartime injuries, there are limited data on patient outcomes following civilian prehospital use and no data on the use in rural trauma. METHODS: We performed a multi-institutional retrospective analysis of clinical outcomes following prehospital use of QuikClot combat gauze (QC) and combat application tourniquets (CATs) from 2009 to 2014. The primary outcome measured was effectiveness. Secondary outcomes included morbidity, mortality, patients' demographics, injury characteristics, and hospital outcomes. RESULTS: Between 2009 and 2014, 95 patients were managed by prehospital personnel with QC and/or CAT. Forty received QC, 61 received CAT, and 6 received both products. The median age was 40 years (6–91 years), 29% were female, and the median injury severity score was 7 (1–25). QuikClot combat gauze was 89% effective. Minimal morbidity was associated with QC use. Combat application tourniquet was 98% effective. Median tourniquet time was 21 minutes (6–142 minutes), the median injury severity score was 9 (1–50), and mortality was 9.8%. Morbidities observed with tourniquet use included amputation, fasciotomy, rhabdomyolysis, and acute kidney injury. Risk of amputation was associated with higher injury severity ( p = 0.04) but not with elderly age, obesity, or the presence of medical comorbidities. No amputations resulted solely from the use of tourniquets. CONCLUSIONS: QuikClot combat gauze and CAT are safe and effective adjuncts for hemorrhage control in the rural civilian trauma across a wide range of injury patterns. In a rural civilian population including women, children, and elderly patients with medical comorbidities, these devices are associated with minimal morbidity beyond that of the original injury. LEVEL OF EVIDENCE: Therapeutic study, level V.